2009
DOI: 10.1186/1757-1626-2-1
|View full text |Cite
|
Sign up to set email alerts
|

Stent angioplasty of narrowed portocaval shunt in Budd Chiari syndrome: a case report

Abstract: BackgroundHepatic vein thrombosis (Budd-Chiari Syndrome) is a rare disorder resulting from an obstruction to the outflow of blood from the liver. Early decompression is needed to prevent liver dysfunction and death. Radiological intervention includes angioplasty of stenosis and webs and the placement of transjugular intrahepatic portosystemic shunts (TIPPS). Side-to-side portacaval shunt (SSPCS) remains the gold standard for achieving good long-term results.Case presentationA 37-year old lady underwent side-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 11 publications
0
28
0
Order By: Relevance
“…The neoplasms include Schwannomas, meningiomas, and ependymomas and thus NF2 is also known as MISME, which stands for multiple inherited Schwannomas, meningiomas, and ependymomas. The presence of bilateral vestibular Schwannomas is a defining feature, and as many as 10% of patients with this tumor have neurofibromatosis type 2 [1] , [2] , [3] .…”
Section: Introductionmentioning
confidence: 99%
“…The neoplasms include Schwannomas, meningiomas, and ependymomas and thus NF2 is also known as MISME, which stands for multiple inherited Schwannomas, meningiomas, and ependymomas. The presence of bilateral vestibular Schwannomas is a defining feature, and as many as 10% of patients with this tumor have neurofibromatosis type 2 [1] , [2] , [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, only few studies in literature report the combination of PAH with aHUS in cblC defect. In 2009, Profitlich et al first described a 3-year-old child with already known cblC defect presenting with right heart failure and PAH, with complete resolution after aggressive medical management [ 9 ]. Compared to this case, our patient had previously been completely asymptomatic before and the negativity of neonatal screening complicated the diagnostic procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate of RSH is about 4%, but in iatrogenic cases, it is 18%, and in cases of RSH induced by anticoagulants, it can even reach 25%. 9 Studies have indicated that RSH in the lower abdomen is usually caused by the rupture of the inferior epigastric artery. In an emergency, ligation of this artery may help to prevent shock caused by massive bleeding as well as secure more time for further surgical treatment.…”
Section: Discussionmentioning
confidence: 99%